Tax Collection and Its Issues in Indonesia - Tomy, Chairian; Nofitasari, Susi (Global Journal of Taxation and Fiscal Policy, 2025)
Taxes are mandatory payments that private individuals or organizations must make to the state; they are enforced by law, and the money collected is utilized for the state's benefits and the welfare of the populace. To regulate the tax legislation, specifically: a set of regulations that control the interaction between the government, which collects taxes, and the taxpayers. The following factors contributed to the numerous issues with tax collection in Indonesia: a lack of socialization, a lack of regulation in the taxation itself, a low level of awareness, knowledge, and economic status, an incomplete and inaccurate database, and a lack of consistent and firm law enforcement in the form of supervision and sanctions. To deal with the tax reforms, among other things: enhancing the regulations and set of rules; promoting socialization to increase knowledge and awareness of the tax-abiding taxpayer; evaluating; providing a database that is comprehensive, accurate, integrated, and guaranteed confidentiality; enhancing law enforcement in terms of supervision and sanctions in a consistent and firm manner; and collecting taxes: Fair, compliant with the law, economical, effective, and the system ought to be straightforward.